PAUF as a Target for Treatment of High PAUF-Expressing Ovarian Cancer - Kim, Yeon Jeong; Jiang, Fen; Park, Jin; Jeong, Hyeon Hee; Baek, Ji Eun; Hong, Seung-Mo; Jeong, Seong-Yun; Koh, Sang Seok (Frontiers in Pharmacology, 2022)
Pancreatic adenocarcinoma up-regulated factor (PAUF) plays an important role in tumor growth, metastasis, and immune evasion in the pancreatic tumor microenvironment, and recent studies suggest an association between PAUF expression and poor prognosis in ovarian cancer patients. The current study aimed 1) to characterize the potential tumor-promoting role of PAUF in ovarian cancer, using in vitro and in vivo models, including a PAUF-knockout OVCAR-5 cell line, and 2) to explore the potential therapeutic effects of an anti-PAUF antibody for ovarian cancer. Recombinant PAUF significantly increased tumor metastatic capacity (migration, invasion, and adhesion) in all the ovarian cancer cell lines tested, except for the OVCAR-5 cell line which expresses PAUF at a much higher level than the other cells. PAUF-knockout in the OVCAR-5 cell line led to apparently delayed tumor growth in vitro and in vivo. Furthermore, the administration of an anti-PAUF antibody exhibited notable sensitizing and synchronizing effects on docetaxel in mice bearing the OVCAR-5 xenograft tumors. Taken together, this study shows that the expression level of PAUF is an independent factor determining malignant behaviors of ovarian cancer and, for the first time, it suggests that PAUF may be a promising therapeutic target for high PAUF-expressing ovarian cancer.